2017
DOI: 10.18517/ijaseit.7.1.1180
|View full text |Cite
|
Sign up to set email alerts
|

Kenaf Fiber Composite in Automotive Industry: An Overview

Abstract: Recently, natural fibers become attractive to automotive industry as an alternative reinforcement for glass fiber reinforced thermoplastics. Additionally, natural fiber components in the automotive industry can provide numerous advantages compared to synthetic conventional such as reduction of weight and cost, recyclability, renewability and in addition to eco-efficiency. Thus, the use of natural fibers in the automotive industry has shown increasingly stringent environmental criteria. Furthermore, amongst gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 24 publications
(28 reference statements)
0
46
0
2
Order By: Relevance
“…The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11]. A study on KCF-reinforced unsaturated polyester composite revealed that 20 wt % of KCF reinforcements is the benchmark to enhance the composite's mechanical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The plant's core resembles wood and makes up 60-70% of the stem's dry weight; bark fibers contribute to the remaining 30-40%, and have a dense structure [9]. Several studies have reported the use of kenaf core fibers (KCF) as reinforcements in composite panels [10,11]. A study on KCF-reinforced unsaturated polyester composite revealed that 20 wt % of KCF reinforcements is the benchmark to enhance the composite's mechanical properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid kenaf/glass fiber composites have shown properties comparable to the glass fiber composite as brake lever in automotive [101]. Furthermore, natural/glass fiber hybrid composites have manifested reduced moisture absorption compared to the natural fiber composites increasing their chances in structural applications [68,102,103]. Flax/glass hybrid composite in epoxy was studied for marine applications and showed enhanced aging durability in marine environmental conditions [63].…”
Section: Applications Of Hybrid Compositesmentioning
confidence: 99%
“…It is based on 70% natural fibers and provides up to 50 % weight reduction compared to the conventional metal-reinforced sunroofs [106]. The efforts [4,67,100,102,103] to partially replace conventional fiber reinforced composites with better performing and environmentally-friendly materials are evident from the literature review [107][108][109]. The demand of such composites is almost constant in the automotive industry because of their suitable properties for this sector such as low density, CO 2 footprint, and good crash behavior [110].…”
Section: Applications Of Hybrid Compositesmentioning
confidence: 99%
“…Serat kenaf mendapat perhatian kalangan industri dalam 10 tahun terakhir karena berbagai produk diversifikasi yang dihasilkan serat kenaf. Produk diversifikasi serat kenaf adalah bahan baku tekstil (Indriani et al, 2013), produk fashion (Masykur & Puspitasari, 2019), kertas lainer (Kardiansyah & Sugesty, 2014;Tahir et al, 2011), industri otomotif (Hassan et al, 2017), konstruksi (Akil et al, 2015, dan lain-lain. Beberapa keunggulan serat kenaf terdapat pada hal biaya, kepadatan, keterbaruan, daur ulang, abrasivitas dan biodegradasi (Jeyanthi & Rani, 2012).…”
Section: Pendahuluanunclassified